Contribution of the deep ocean to the centennial changes of the Indonesian Throughflow. Issue 6 (31st March 2017) - Feng, Ming; Zhang, Xuebin; Sloyan, Bernadette; Chamberlain, Matthew
Abstract: The Indonesian Throughflow (ITF) is an important component of the global overturning circulation. In this study, we amend Godfrey's Island Rule to estimate the ITF transport by including contributions from deep ocean vertical transport. Simulations using a near‐global 1/10° ocean general circulation model are used to verify the amended Island Rule. We show that deep ocean circulation is as important as wind‐driven processes to the ITF transport and variability. The centennial weakening of the ITF by 32% during the 21st century, under the high greenhouse gas emission scenario, is primarily associated with reductions in net deep ocean upwelling in the tropical and South Pacific. Deep ocean circulation of the Pacific may become less connected with the ITF transport in a warm climate. Key Points: We have amended Godfrey's Island Rule by including the Pacific Ocean deep upwelling in the estimation of the ITF volume transport Both wind‐driven and overturning circulations contribute to the decadal to centennial changes of the Indonesian Throughflow The weakening of deep upwelling in the Pacific is the main contributor to the ITF transport reduction under the global warming Plain Language Summary: This study makes an attempt to formalize the relationship between the communication between the upper ocean and deep ocean circulations in determining the volume transport of the Indonesian Throughflow. It is demonstrated that the deep ocean upwelling contribution is as important as the wind‐driven circulation in the mean and variability of the Indonesian Throughflow transport. The centennial declining trend of the Indonesian Throughflow transport in the climate models under the influence of the global warming is mostly due to the weakening trend of the deep ocean upwelling in the Pacific Ocean, which indicate that there will be less communication between the wind‐driven circulation and the deep ocean overturning circulation in the future climate.